DISCOURSE AWARENESS AND ISSUES IN EST MATERIALS DESIGN - Shameem Rafik Galea (Universitas Katolik Indonesia Atma Jaya, 2005)
Understanding text structure (knowledge of discourse and genre) within specific contexts plays a very important part in EST materials development for language teaching and learning. It is argued that for students to comprehend particular texts and to learn a language well, language teaching should begin with an understanding of text structure. It is thus essential for EST teachers to be aware that linguistic patterns exist across stretches of text within different text types and an understanding of these patterns would make text comprehension and reading to learn in the content area easier. Thus, teachers need to be trained to develop discourse-based materials as an understanding of different text types can enhance language learning. This paper discusses the importance of discourse awareness and issues of design, development and application in the development of EST materials in relation to written texts by introducing frameworks for designing discourse-based materials. Keywords: discourse awareness, EST materials design